INFORMATION TECHNOLOGY INTEGRATED EDUCATION, A HARD ROAD TO TRAVEL FOR LAME DUCKS: BLENDED INSTRUCTIONAL DELIVERY, POTENTIALS FOR LEARNING AFFORDANCES FOR ELT STUDENTS, UNIVERSITÉ FELIX HOUPHOUËT BOIGNY, CÔTE D’IVOIRE - Diarassouba, Sidiky (International Journal of Research -GRANTHAALAYAH, 2017)
Increasingly, matters relating to formal education have been moving away from secular formats to more technology-oriented ones, such as online and various distance teaching and learning networking arrangements. While advanced educational systems have been being carried in a general momentum towards these newer information technology integrated instructions, the vast majorities of countries worldwide lag behind. Such ones are those from the developing world, in general, and particularly most African countries. Among the main reasons, as it appears the culture of these newer ways of doing education and issues regarding the external environment are prominent candidates. Consequently, it is hard for all those countries to actually be on board. However, there seem glimpses of hope to benefit from advances in technological innovation even in underprivileged areas. To what extent can some forms of information technology be incorporated in education, and to what avail? Such was the central questioning which this research project tried to address. It turned out that forms of blended instructional formats were viable solutions given the many teaching and learning affordances they embody. A major contention that transpired from this study was that, based on their particular circumstances, instructors would be much better off considering the use of some forms of integration of new technologies in their instructional design than no integration at all, pending better auspices.